2018
DOI: 10.3389/fneur.2018.00495
|View full text |Cite
|
Sign up to set email alerts
|

A Voxel-Wise Meta-Analysis of Gray Matter Abnormalities in Essential Tremor

Abstract: Objective: To identify the consistent gray matter (GM) volume changes from the whole brain voxel-based morphometry (VBM) studies on essential tremor (ET).Methods: The whole brain VBM studies comparing ET patients and healthy controls (HCs) were systematically searched in the PubMed, Embase and Web of Science from January 2000 to December 2017. Coordinates with significant differences in regional GM volume between ET patients and HCs were extracted from included studies and the meta-analysis was performed using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 56 publications
1
21
0
Order By: Relevance
“…55 showed different findings, with compensatory increase of the gray matter in the cerebellum and other brain areas, 18,19 rather than atrophy showed by older studies. 55 showed different findings, with compensatory increase of the gray matter in the cerebellum and other brain areas, 18,19 rather than atrophy showed by older studies.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…55 showed different findings, with compensatory increase of the gray matter in the cerebellum and other brain areas, 18,19 rather than atrophy showed by older studies. 55 showed different findings, with compensatory increase of the gray matter in the cerebellum and other brain areas, 18,19 rather than atrophy showed by older studies.…”
Section: Discussionmentioning
confidence: 89%
“…It could be accepted that studies, where no cerebellar signs or other neurological deficits mentioned, have used only essential tremor patients, but whether their findings could be reliable is still questionable while they had not used the new diagnostic criteria and there is a strong risk of patients with different types of tremor may have been included. Most recent studies using the new classification for tremor and the new diagnostic criteria for essential tremor showed different findings, with compensatory increase of the gray matter in the cerebellum and other brain areas, 18,19 rather than atrophy showed by older studies. [10][11][12][13][14][15] Further studies which will consider the new classification of tremor and will rigorously apply the new diagnostic criteria for essential tremor and which will categorize patient based on both clinical phenotypes and the etiology needed in order to clarify the microscopic and macroscopic changes in essential tremor.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Articles were excluded if (1) sufficient information could not be obtained even after contacting the authors; (2) GMV differences were reported only in regions of interest; (3) the article was not peer‐reviewed; (4) there were less than 10 subjects in either the PD or HC group; (5) the studies used overlapping data published in previous VBM studies – in this case, only the study with the largest size group was selected. The quality of each study was evaluated using a 13‐item checklist, which had been used in previous meta‐analyses .…”
Section: Methodsmentioning
confidence: 99%